2009
DOI: 10.1093/intimm/dxp034
|View full text |Cite
|
Sign up to set email alerts
|

Irradiated CIITA-positive mammary adenocarcinoma cells act as a potent anti-tumor-preventive vaccine by inducing tumor-specific CD4+ T cell priming and CD8+ T cell effector functions

Abstract: In the present study, we investigated the possibility to use irradiated, non-replicating class II transcriptional activator (CIITA)-transfected tumor TS/A cells as a cell-based vaccine. Eighty-three percent of TS/A-CIITA-vaccinated mice were completely protected from tumor growth and the remaining 17% displayed significant reduction of tumor growth. In contrast, only 30% of mice injected with irradiated TS/A parental cells were protected from tumor growth, whereas the remaining 70% of animals remained unprotec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 32 publications
1
40
0
Order By: Relevance
“…[11][12][13][14] In this study, we extended this observation to tumor cells of the H-2 b genetic background, which at variance with H-2 d genotype can express only one of the two MHC-II molecules, the IA but not the IE molecule. Two distinct MHC-II-negative tumor cell lines, the MC38 colon carcinoma and the LLC Lewis lung carcinoma, highly tumorigenic in vivo, became strongly immunogenic after de novo expression of MHC-II molecules mediated by CIITA transfection.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…[11][12][13][14] In this study, we extended this observation to tumor cells of the H-2 b genetic background, which at variance with H-2 d genotype can express only one of the two MHC-II molecules, the IA but not the IE molecule. Two distinct MHC-II-negative tumor cell lines, the MC38 colon carcinoma and the LLC Lewis lung carcinoma, highly tumorigenic in vivo, became strongly immunogenic after de novo expression of MHC-II molecules mediated by CIITA transfection.…”
Section: Discussionmentioning
confidence: 84%
“…In tumor cells of the H-2 d genetic background, expressing both IA and IE molecules, this approach has proven to be particularly successful since we could demonstrate that highly tumorigenic cells of both epithelial and connective tissue origin (carcinomas and sarcomas), rendered MHC-II-positive upon CIITA transfection, not only could be rejected or strongly delayed in their growth when injected in syngeneic immunocompetent recipients (Balb/C mice), but also could stimulate an anamnestic response capable to induce rejection of parental untransfected, MHC-II-negative cells. [11][12][13][14] Importantly, protective immunity could be transferred to na€ ıve syngeneic Balb/C mice by injecting CD4 C TH cells from mice "vaccinated" with CIITA-transfected tumor cells. 13,14 All together, our previous results indicated that MHC-II molecules expressed in tumor cells were necessary to induce a potent adaptive immune response against the tumor in vivo, that this response was mastered by CD4…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our study was distinguished from several studies reported by others that used tumor cells modified with CIITA gene as cancer vaccine (Armstrong et al, 1997;Mortara et al, 2009). By using exosomes, we could expect fewer side effects than when tumor cells themselves were used.…”
Section: Discussionmentioning
confidence: 83%
“…At some point in their natural history, most tumors are able to present antigens and act as antigen-presenting cells (APCs) 17 . However, the lack of co-stimulatory molecules on tumor cells promote tolerance, thus exerting detrimental effects.…”
Section: Tumor Cells As Antigen-presenting Cellsmentioning
confidence: 99%